2018
DOI: 10.1108/ec-07-2017-0258
|View full text |Cite
|
Sign up to set email alerts
|

Use of adaptive neuro-fuzzy inference system and gene expression programming methods for estimation of the bearing capacity of rock foundations

Abstract: Purpose This study aims to examine the potential of two artificial intelligence (AI)-based algorithms, namely, adaptive neuro-fuzzy inference system (ANFIS) and gene expression programming (GEP), for indirect estimation of the ultimate bearing capacity (qult) of rock foundations, which is a considerable civil and geotechnical engineering problem. Design/methodology/approach The input-processing-output procedures taking place in ANFIS and GEP are represented for developing predictive models. The great importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Results in Figure 6 and Table 3 also show a comparison of the model proposed in this paper and our recent VRI-GEP technique [29]. It can be observed that both the GEP and ANFIS techniques provide more accurate results than other techniques in the literature [39,40]. Reference [29] employed the GEP technique to develop a VRI model whereas in this paper, the ANFIS-DWT model is used to estimate the power output directly without calculating the VRI as per the strategy of all existing models in the literature.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Results in Figure 6 and Table 3 also show a comparison of the model proposed in this paper and our recent VRI-GEP technique [29]. It can be observed that both the GEP and ANFIS techniques provide more accurate results than other techniques in the literature [39,40]. Reference [29] employed the GEP technique to develop a VRI model whereas in this paper, the ANFIS-DWT model is used to estimate the power output directly without calculating the VRI as per the strategy of all existing models in the literature.…”
Section: Discussionmentioning
confidence: 73%
“…Results in Figure 6 and Table 3 also show a 83 comparison of the model proposed in this paper and our recent VRI-GEP technique [29]. It can be 84 observed that both the GEP and ANFIS techniques provide more accurate results than other 85 techniques in the literature [39,40]. Reference [29]…”
mentioning
confidence: 82%
“…Some metrics are used to verify the ANFIS prediction (Dao and Huang, 2015a; Sadrossadat et al , 2018) as follows:…”
Section: Numerical Analysis and Optimization Implementmentioning
confidence: 99%
“…Artificial intelligence (AI) predictions such as those made by artificial neural networks (ANN) commonly offer results that are significantly more accurate than predictions generated by either analytical models or design guidelines. However, ANN has been characterized as “black-box” models due to the extremely large numbers of nodes and connections within their layered structures (Tsai, 2009; Tsai, 2010; Öztekin, 2016; Vardhan et al , 2017; Yan and Lin, 2017; Sadrossadat et al , 2018). Since it was first proposed by Koza (1992), genetic programming (GP) has garnered considerable research attention because of its ability to model nonlinear relationships for input–output mappings without assuming the prior form of these relationships.…”
Section: Introductionmentioning
confidence: 99%